2021
DOI: 10.11648/j.sd.20210903.18
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of a Carborane-containing Precursor for B<sub>4</sub>C Ceramics

Abstract: B 4 C ceramic is one of widely used ceramics with properties of low density, high hardness, high thermal-stability and high neutron absorption cross-section. However, the high melting point and high hardness of B 4 C make it difficult to be prepared as materials with complex shape. Precursor derived method is an effective approach to prepare special-shaped ceramics. In the early research of B 4 C ceramic precursors, highly toxic and unstable decaborane was generally used as the boron source material, and precu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The preparation of boron carbide through the pyrolysis of various carborane-containing polymers has been described [ 137 , 138 , 139 , 140 ]. The Ni-catalyzed polymerization of 1,2-bis(4-chloro-phenyl)- ortho -carborane leads to poly(phenylene- ortho -carborane).…”
Section: Carborane As a Boron Source For Boron-containing Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…The preparation of boron carbide through the pyrolysis of various carborane-containing polymers has been described [ 137 , 138 , 139 , 140 ]. The Ni-catalyzed polymerization of 1,2-bis(4-chloro-phenyl)- ortho -carborane leads to poly(phenylene- ortho -carborane).…”
Section: Carborane As a Boron Source For Boron-containing Materialsmentioning
confidence: 99%
“…It was found that the heating of the polymer at 1000–1200 °C resulted in the crystallization of boron carbide, according to the X-ray powder diffraction studies [ 139 ]. The Ni-catalyzed polymerization of 1,7-bis(4-chlorophenyl)- meta -carborane produces poly(phenylene- meta -carborane), which can be used as a novel boron carbide precursor [ 140 ]. Due to its high ceramic yield, it can be used to prepare boron carbide ceramics with different shapes [ 141 ].…”
Section: Carborane As a Boron Source For Boron-containing Materialsmentioning
confidence: 99%
“…Therefore, acquiring the technical knowledge of B4C production, achieving its manufacturing technology from available raw materials, as well as using cost-effective fabrication methods are of special importance [8][9][10]. There are various techniques for synthesis of B4C ceramics including carbothermal reduction [11,12], synthesis from its elemental constituents [13,14], magnesiothermal reduction [15,16], chemical vapor deposition (CVD) [17][18][19], and synthesis from polymeric raw materials [20][21][22]. Among the above methods, the synthesis using constituent elements is not cost-effective due to the expensive pure raw materials required and is merely a research-based methodology for synthesis in the laboratory [23].…”
Section: Introductionmentioning
confidence: 99%
“…Boron carbide is widely employed in strategic industrial applications due to its fascinating characteristics such as low density (2.5 g/cm 3 ), high hardness and wear resistance, high melting temperature (2445 °C), and inertness against chemicals [1][2][3][4][5][6]. Synthesis from its elemental constituents [7,8] or polymeric raw materials [9][10][11], magnesiothermal [12,13] or carbothermal reduction [14,15], and chemical vapor deposition [16][17][18] are the main manufacturing processes for the production of B 4 C ceramics. Although the B 4 C is usually synthesized through the high temperature carbothermal reduction of B 2 O 3 , the evolution of the carbothermal reduction for organic precursors to synthesize B 4 C is receiving considerable curiosity [19].…”
Section: Introductionmentioning
confidence: 99%